IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society 2011
DOI: 10.1109/iecon.2011.6119881
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature monitoring by a wireless sensor

Abstract: The present paper reports the development of a temperature data logger based on a temperature sensitive resistive film and an RFID tag. Thanks to its capability of wireless communication, the device is going to be used for a minimally invasive remote monitoring of the skin temperature under a bandage or a wound dressing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…For instance, wireless temperature sensors based on thermo-resistivity of carbon nanotubes can predict initiation of pressure ulcers and upcoming inflammation 116 . The laboratory research showed a great promise and these sensors were further tested on healthy volunteers.…”
Section: Temperature As a Parameter For Wound Diagnosismentioning
confidence: 99%
“…For instance, wireless temperature sensors based on thermo-resistivity of carbon nanotubes can predict initiation of pressure ulcers and upcoming inflammation 116 . The laboratory research showed a great promise and these sensors were further tested on healthy volunteers.…”
Section: Temperature As a Parameter For Wound Diagnosismentioning
confidence: 99%
“…Resistance-temperature curve shows that the sensor is linear for temperature in the range of 0 ℃ to 120 ℃ with a slope of 2.7 Ω/ ℃. Matzeu et al, developed a wireless thermistor sensor based on resistive carbon nanotube film and radio frequency identification (RFID) tag [102]. The team did not find a linear relationship between temperature and resistance.…”
Section: Temperature Sensorsmentioning
confidence: 99%
“…However, there is scarce research material available focusing on incorporating temperature measurements within wound dressings. A wireless sensing system based on a radio frequency identification (RFID) tag has been proposed by Matzeu et al 26 for the real-time monitoring of the skin temperature. The sensor was fabricated using multiwall carbon nanotubes and the electrodes were prepared by electroplating nickel and gold over the copper tracks prepared through a lithography process.…”
Section: Sensing Of Wound Temperaturementioning
confidence: 99%